Advances in Intelligent, Interactive Systems and Applications Proceedings of the 3rd International Conference on Intelligent, Interactive Systems and Applications (IISA2018) - Xhafa, Fatos; Patnaik, Srikanta; Tavana, Madjid (Advances in Intelligent Systems and Computing, 2019)
This book presents the proceedings of the International Conference on Intelligent, Interactive Systems and Applications (IISA2018), held in Hong Kong, China on June 29-30, 2018. It consists of contributions from diverse areas of intelligent interactive systems (IIS), such as: autonomous systems; pattern recognition and vision systems; e-enabled systems; mobile computing and intelligent networking; Internet & cloud computing; intelligent systems and applications. The book covers the latest ideas and innovations from both the industrial and academic worlds, and shares the best practices in the fields of computer science, communication engineering and latest applications of IOT and its use in industry. It also discusses key research outputs, providing readers with a wealth of new ideas and food for thought.